Optimizing agricultural sustainability: enriched organic formulations for growth, yield, and soil quality in a multi-crop system - Garg, Kamal; Dhar, Shiva; Sharma, Vinod Kumar; Azman, Elisa Azura; Meena, Rajendra Prasad; Hashim, Mohammad; Kumar, Dileep; Ali, Ghous; Karunakaran, Vetrivel; Kumar, Yogesh; Athnere, Sonal; Kumar, Sourabh; et al. (Frontiers in Plant Science, 2024)
Utilizing agricultural and industrial wastes, potent reservoirs of nutrients, for nourishing the soil and crops through composting embodies a sustainable approach to waste management and organic agriculture. To investigate this, a two-year field experiment was conducted at ICAR-IARI, New Delhi, focusing on a pigeon pea–vegetable mustard–okra cropping system. Seven nutrient sources were tested, including a control (T1), 100% recommended dose of nitrogen (RDN) through farmyard manure (T2), 100% RDN through improved rice residue compost (T3), 100% RDN through a paddy husk ash (PHA)-based formulation (T4), 75% RDN through PHA-based formulation (T5), 100% RDN through a potato peel compost (PPC)-based formulation (T6), and 75% RDN through PPC-based formulation (T7). Employing a Randomized Block Design with three replications, the results revealed that treatment T4 exhibited the significantly highest seed (1.89±0.09 and 1.97±0.12 t ha-1) and stover (7.83±0.41 and 8.03±0.58 t ha-1) yield of pigeon pea, leaf yield (81.57±4.69 and 82.97±4.17 t ha-1) of vegetable mustard, and fruit (13.54±0.82 and 13.78±0.81 t ha-1) and stover (21.64±1.31 and 22.03±1.30 t ha-1) yield of okra during both study years compared to the control (T1). Treatment T4 was on par with T2 and T6 for seed and stover yield in pigeon pea, as well as okra, and leaf yield in vegetable mustard over both years. Moreover, T4 demonstrated notable increase of 124.1% and 158.2% in NH4-N and NO3-N levels in the soil, respectively, over the control. The enhanced status of available nitrogen (N) and phosphorus (P) in the soil, coupled with increased soil organic carbon (0.41%), total bacteria population (21.1%), fungi (37.2%), actinomycetes (44.6%), and microbial biomass carbon (28.5%), further emphasized the positive impact of T4 compared to the control. Treatments T2 and T6 exhibited comparable outcomes to T4 concerning changes in available N, P, soil organic carbon, total bacteria population, fungi, actinomycetes, and microbial biomass carbon. In conclusion, treatments T4 and T6 emerge as viable sources of organic fertilizer, particularly in regions confronting FYM shortages. These formulations offer substantial advantages, including enhanced yield, soil quality improvement, and efficient fertilizer utilization, thus contributing significantly to sustainable agricultural practices.